The Impact of Technology on Safe Medicines Use and Pharmacy Practice in the US - Schneider, Philip J. (Frontiers in Pharmacology, 2018)
For decades it has been suggested that pharmacists are under-utilized and could better use their knowledge and experience to improve the use of medicines. The traditional roles for pharmacists have been preparing and distributing medicines, but this has limited both the location where they work and the available time to work more closely with other healthcare professionals to improve both the effectiveness and safety of medicines. Newly emerging technologies have made this possible. Examples include robotics that automate preparation and distribution of medicines, electronic health information, clinical decision support systems, and machine readable coding on medicine packaged. As a result of the use of these technologies, pharmacists in hospitals are working outside the hospital pharmacy and spending more time in medication therapy management activities compared to traditional distribution roles.